Industry 5.0 transition for an advanced service provision - Farsi, Maryam; Erkoyuncu, John Ahmet (SSRN, 2021)
The current service provision for high-value manufactured equipment is transitioning from a purely product-focused business model to a service-focused one, known as servitization. Businesses aim to continuously improve their service offerings to sustain customer satisfaction in order to maintain their competitive edge within the industry. On the other hand, Industry 5.0 is characterized by bringing industries’ focus towards collaboration for sustainable value co-creation rather than producing goods and services for profit. This research investigates the possible enablers to design and deploy a highly effective advanced service provision. Advanced service provision refers to providing service solutions that fulfil the desirable availability, capability, and reliability in product-service contracts. The research outcomes are presented in the form of a transition framework and a set of recommendations towards the desired future state, with phased timings for implementing the key enablers with a potential 2035 vision to support the Industry 5.0 transition. The validity of the framework was tested by collecting experts’ opinion who currently work within servitization contracts. The outcome of this study can be generalized for industries in high-value manufacturing.
Keywords: Industry 5.0; Industry 4.0; Servitization; Maintenance; Reliability; High-Value Manufacturing